Assessing trainees' oral performance in a Chilean teacher training program: a corpus-based study - Ortega, Maritza Fernanda (Colombian Applied Linguistics Journal, 2014)
The present paper reports the implementation of syllabus innovations in EFL teacher education in Chile after diagnosing a lack of language achievement standards common to all EFL teacher training programs offered in public and private universities alike. The aim of this study is to collect linguistic data in natural and artificial social contexts – EFL trainees’ intermediate status between their native language (Spanish) and the target language (English) – in order to create the first Chilean corpus of spoken English as a foreign language, in the interest of analyzing the errors that are most likely to be made and fossilized by native speakers of Chilean Spanish. Once the results of this exercise are available, EFL trainers, professors, and SLA researchers will be able to design a newly sequenced syllabus based on the Content-based Approach and tailored to students’ needs so as to enhance oral performance in L2 English.